Avaliação da biodisponibilidade relativa/bioequivalência entre duas formulações de Lansoprazol 30 mg em voluntários sadios de ambos os sexos - Lemos, Ana Paula Dajtenko (2019)
After the publication of RDC nº133 and nº134 by the National Agency of Sanitary Vigilance in 2003 which determined the obligation to carry out studies of relative bioavailability for similar, it was possible to guarantee the safe and effective interchangeability between such medicines and the reference ones, equating the pharmacokinetic and pharmacodynamic profile of both. The present study aimed to compare the relative bioavailability/ bioequivalence between two formulations of Lansoprazole 30 mg as a hard gelatin capsule in 60 healthy volunteers of both sexes, with a mean age of 24.4 (± 2.45) years. An open, randomized, cross-over study was carried out with two periods in which the volunteers received in each period one capsule of the test drug (T) or the reference medicine (R) followed by blood sampling at regular intervals if the washout of 7 days between one period and another. The determination of the drug in the blood plasma was performed by HPLC-MS/ MS. The statistical step was performed using the Phoenix WinNonlin Professional Network Edition 7.0 software to calculate the 90% confidence interval (IC90) constructed for the ratio of the geometric means of the parameters Cmax, ASC0-t, ASC0-inf which should be within the range of 80-125%. The values obtained for the parameter Cmax, 1094.29 ng/mL (R) and 1176.70 ng/mL (T), ASC0-t, 4081.28 ng.h/mL (R) and 4120.02 ng.h /mL (T) and ASC0-inf, 4208.88 ng.h/mL (R) and 4254.92 ng.h/mL (T) were consistent with previous studies. For the Cmax parameter IC90 was obtained from 100.43% -115.3%, ASC0-t obtained IC90 of 97.64% -104.36% and ASC0-inf, IC90 of 97.29% - 105.04%, considering the test formulation x reference respectively. By analyzing the results of IC90 for Cmax, ASC0-t, ASC0-inf it can be inferred that the test formulation is bioequivalent to the reference formulation for speed and extent of absorption.